Une approche pédagogique d'enseignement du français langue seconde ajustée aux étudiants venant des programmes d'immersion - Peguret, Muriel (Canadian journal of applied linguistics, 2014)
This study focuses on the circumstances of post-immersion students in their first year of French language study at university. It seeks to assist them in surpassing the plateau level of communication (Lyster, 2007). It views the issue in terms of students' use of reflexivity, specifically a lack of engagement to learning strategies and long-term autoregulation. Our study views this situation as relating to an instrumental understanding of language and language learning. Our hypothesis is supported by an analysis of the responses given by 82 students to two open-ended questions, which provides insight into their use of strategy. A chi-square test reveals an extremely significant difference between students with a background in early immersion or French school, and those from other French as a second language programs: the former use fewer strategies in their writing than the latter. We therefore propose a pedagogical approach that aims to reactivate our students' reflexivity. [PUBLICATION ABSTRACT]